Pengaruh Perebusan Filet Ayam Broiler dengan Mengunakan Daun Mayana (Solenostemon scutellarioides (L)) Terhadap Kadar Air, Protein dan Lemak - Aloysia Tenny Damayanti Indriastuti; Irine Ike Praptiwi (AGRICOLA, 2015)
Meat of broilerchicken is one of the many sources of animal protein circulating in the market, but the fat content in broiler meat does not make a lot of interest.This research aims to know the fat content of broiler meat that use boiled leaf mayana (Solenostemon scutellarioides (L.)), it is expected to do the boiling use leaf mayana (Solenostemon scutellarioides (L.)), the fat content of chicken broiler meat have to be reduced so that the quality of meat being better and more healthy for consumption.This study used a randomized complete design (RAL) with 4 treatments and three replicates, treat include the use of leaf mayana (Solenostemon scutellarioides (L.)) as much as 0, 100, 200, 300 grams.Variables observed in the form of a fat content. The results obtained showed that boiling filet use mayana leaf (Solenostemon scutellarioides (L.)) up to 300 grams in moisture content, protein content and fat content tended to decline but not significant effect.